Interactive Articulate Storyline 3-Based Learning Media: Enhancing Student Engagement and Knowledge in Elementary Dance Arts Education - Azzahra, Aulia; Nurharini, Atip (Indonesian Journal of Educational Research and Review, 2024)
The limited use of effective learning media by teachers often leads to low student engagement during lessons, highlighting the need for innovative tools that can help students quickly grasp the material. This study aims to develop an interactive learning media based on Articulate Storyline 3 for the fifth-grade Dance Arts subject, focusing on the diversity of dance supporting elements. This research follows a development methodology using the ADDIE model (Analyse, Design, Develop, Implement, and Evaluate). The study's subjects include one Dance Arts subject matter expert, one instructional media expert, one practitioner, six students for a small-scale trial, and 20 students for a large-scale trial. The data analysis techniques employed are both quantitative and qualitative. The developed media comprises several features, including a cover page, student identity section, navigation menu, detailed material explanation, instructional videos, and a quiz or evaluation section for students. The findings indicate that the interactive media significantly enhances student learning outcomes, particularly in increasing their knowledge of the subject matter. Additionally, the media's interactive features and visually engaging content foster greater student enthusiasm and active participation in learning. This research demonstrates the potential of Articulate Storyline 3-based interactive media as an effective tool for improving the quality of elementary school education, particularly in creative arts subjects.